PENGEMBANGAN KURIKULUM MADRASAH DI DAERAH TRANSISI - Sukino Sukino (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2017)
Madrasah is a populist educational institution in the midst of the Muslim community in Indonesia, especially in rural and transitional areas. Madrasahs are currently facing rapidly changing societies, such as structural, culture and interactionchange. The change is caused by the rapidity of modernization and globalization. Education in the context of globalization, including education globalization is required to develop an educational system that will produce graduates who have competitiveness from local, national and international levels. To achieve this goal educational institutions need to internalize themselves with the global environment as a positive response to the changes brought about by modernization and globalization. Externalization is the process of adaptation. Adaptation implies the ability of a community group or an individual to learn and change. Thus the process of adaptation or adjustment refers to the ability of the community to adapt to their environment. The process of adaptation is a positive psychological response in the form of emotional and social change. The form of adaptation that greatly affects the survival and development of madrasah in the transitional area of the global era are curriculum. In the curriculum aspect, madrasahs do not have to replace the existing curriculum, but try to provide development with rational, constructive, and dialogical approaches. While in the aspect of madrasah leadership should begin to prepare a visionary and transformative leadership model. Keywords: Adaptation, Madrasah, Transitional Society